2006
DOI: 10.4161/cbt.5.7.2967
|View full text |Cite
|
Sign up to set email alerts
|

The PERK/eIF2α/ATF4 module of the UPR in hypoxia resistance and tumor growth

Abstract: Hypoxia is a dynamic feature of the tumor microenvironment that contributes to cancer progression. In order to adapt and overcome hypoxic stress, tumor cells activate survival pathways that attempt to couple metabolic processes to reduced energy availability due to oxygen deprivation. While the hypoxia-inducible factors HIF-1 and HIF-2 are critical to the cellular response to hypoxia, HIF-independent processes are known to contribute to this adaptation. Recent evidence demonstrates that hypoxia activates compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(240 citation statements)
references
References 60 publications
7
227
1
5
Order By: Relevance
“…The PERK arm of the UPR also plays important role in tumor proliferation and survival. Inactivation of the PERK pathway by either generating mutations in the kinase domain of PERK or introducing a phosphorylation-resistant form of eIF2a impairs cell survival under extreme hypoxia [83]. Furthermore, PERK limits oxidative DNA damage through Nrf2 activation which further promotes cancer cell proliferation and survival [84].…”
Section: Er Stress and Cancermentioning
confidence: 99%
“…The PERK arm of the UPR also plays important role in tumor proliferation and survival. Inactivation of the PERK pathway by either generating mutations in the kinase domain of PERK or introducing a phosphorylation-resistant form of eIF2a impairs cell survival under extreme hypoxia [83]. Furthermore, PERK limits oxidative DNA damage through Nrf2 activation which further promotes cancer cell proliferation and survival [84].…”
Section: Er Stress and Cancermentioning
confidence: 99%
“…Several cellular conditions, such as high demand for protein synthesis and secretion (3,4), viral infection (5), deprivation of nutrients/oxygen (6,7), and missense mutations affecting both client protein folding (8 -11) and ER folding machinery function (2) enhance protein misfolding and cause accumulation of unfolded or misfolded proteins, leading to ER stress. Mammalian cells use several adaptive mechanisms, collectively known as the unfolded protein response (UPR), to cope with acute ER stress (12).…”
Section: The Endoplasmic Reticulum (Er)mentioning
confidence: 99%
“…(20,23) Recently, the UPR has received considerable attention as a potential target for anticancer therapy. (6,7,10,24) We have shown that versipelostatin (VST), a small molecule compound, can disrupt the UPR during glucose deprivation.(25) Indeed, under that stressor, VST inhibits GRP78 and GRP94 induction and represses the production of the UPR transcription activators ATF4 and X-box protein (XBP)1. VST shows highly selective cytotoxicity to glucose-deprived tumor cells and exerts in vivo antitumor activity at well-tolerated doses.…”
mentioning
confidence: 99%